Human Trafficking: Legal Analysis on Indo-Malaysia Border - Engine Kubota; Fahmi Fairuzzaman; Saman Omar (Journal of Judicial Review, 2023)
Indonesia and Malaysia both face a crisis in combating human trafficking. This crisis includes human trafficking that occurs at the Indonesia-Malaysia border. Indonesia is in Tier 2, while Malaysia is on this issue's Tier 2 watch list. The laws and regulations that Indonesia and Malaysia have in dealing with the issue of human trafficking at the border between the two countries are related. The objectives of this research are (1) to know the provisions and comparison of the laws of the two countries in dealing with human trafficking and (2) to examine the existing rules based on the perspective of international Law to provide input in the renewal of legal science at the national and international levels. This research, which was written using the normative jurisprudence method, found that Indonesia and Malaysia each have specific laws stipulated in Law No. 21/2007 on the Eradication of the Crime of Trafficking in Persons and the Anti-Trafficking in Persons and Anti-Smuggling of Migrants Act 2007 and are involved in bilateral and multilateral cooperation regarding combating human trafficking. The legal efforts that both countries have made still have many shortcomings and require more severe improvements to achieve legal objectives.